An empirical analysis of the coupling and coordinative development of China's green finance and economic growth. (March 2022) - Yin, Xiuling; Xu, Zhaoran
Abstract: This article establishes a comprehensive indicator system for green finance and economic growth, uses a coupling coordination degree model, and selects sample data from 2008 to 2020 to quantitatively explore coordinated development of green finance and economic growth. The following conclusions can be drawn from the research: from 2008 to 2020 years, green finance composite index and economic growth composite index have been improved, and the composite indexes of the two systems have obvious synergy, but China's green finance composite index has been lower than the economic growth composite index, green finance lags behind economic growth. In addition, coupling and coordination degree between China's green finance and economic growth is not high. The period from 2008 to 2020 is basically in the stage of running-in and high-level coordination, and has not reached the stage of extreme coordination. Because green finance cannot be effectively linked to industrial structure adjustment, ecological environmental protection and economic development, and the degree of green finance is not high, it restricts the coordinated development between green finance and economic growth, and causes green finance support to economic growth not obvious. Highlights: Establishes a comprehensive indicator system. Uses a coupling coordination degree model to test relationship. Promoting the healthy development of the financial industry. Provide advice for coordinated development.